The customization and use of psychological capital in an Asian context as a predictor of job satisfaction - Lee, Alex Yi (2011)
In Western countries, psychological capital (PsyCap), made up of the components of self-efficacy, hope, resilience, and optimism, can predict a person’s job satisfaction. This study examines whether this construct can be modified for an Asian context to account for cultural differences between Asians and Westerners, to produce a more accurate measure for predicting job satisfaction. In this study, Asian engineering undergraduates completed a set of questionnaires on the measures of interest. It was found that although a modified psychological capital construct significantly predicted job satisfaction, its correlation to job satisfaction was low. The insertion of kiasuism and defensive pessimism and the removal of optimism did not make any meaningful difference in the ability of psychological capital to predict job satisfaction.